2012
DOI: 10.1002/nau.22201
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Incontinence: Prevalence, Risk Factors, and Impact on Health Related Quality of Life in Saudi Women

Abstract: AimsThe aims of this study were to determine the prevalence, risk factors, and impact upon health related quality of life (HRQL) of urinary incontinence in Saudi women.MethodsWe performed a clinic‐based cross‐sectional survey. 6,600 women aged 20 years and older were selected. The bother of urinary incontinence symptoms was assessed using the Arabic version of the short form of Urogenital Distress Inventory (UDI‐6) questionnaire. We measured the impact of urinary incontinence on HRQL using the Incontinence Imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
67
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 29 publications
8
67
1
2
Order By: Relevance
“…More than 91 % of our participants reported that they had never, or only occasionally, used instrumental coping style, and only 22 % reported previous help-seeking behaviors. A number of other studies have reported low rates of help-seeking behaviors for UI [46,47]. The main reason given for these low rates was that UI was often viewed as a natural, inevitable, or normal consequence of aging or childbirth, rather than a medical condition that required help from healthcare professionals [48][49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…More than 91 % of our participants reported that they had never, or only occasionally, used instrumental coping style, and only 22 % reported previous help-seeking behaviors. A number of other studies have reported low rates of help-seeking behaviors for UI [46,47]. The main reason given for these low rates was that UI was often viewed as a natural, inevitable, or normal consequence of aging or childbirth, rather than a medical condition that required help from healthcare professionals [48][49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…The overall prevalence of urinary incontinence in the Middle East ranges from 20.3% to 54.8% [5,6]. In Qatar it is 20.6%, in the United Arab Emirates it is 20.3% [5,7], in Jeddah and Riyadh, cities of Saudi Arabia were estimated to be 41.4% and 29% respectively [8,9]. There are a number of risk factors for UI which include age, body mass index, medical co-morbidities i.e.…”
Section: Introductionmentioning
confidence: 99%
“…based on the type (2). Sexual dysfunction of women is described as sexual desire, sexual arousal, orgasm and/or sexual pain disorders that cause personal stress (3).…”
mentioning
confidence: 99%